2008
DOI: 10.1002/pmic.200800183
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of embryonic proteome modulation by GA and ABA from germinating rice seeds

Abstract: The phytohormones gibberellic acid (GA) and abscisic acid (ABA) play essential and often antagonistic roles in regulating plant growth, development, and stress responses. Using a proteomics-based approach, we examined the role of GA and ABA in the modulation of protein expression levels during seed germination. Rice seeds were treated with GA (200 microM), ABA (10 microM), ABA followed by GA, GA followed by ABA, and water as a control and then incubated for 3 days. The embryo was dissected from germinated seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 39 publications
1
69
1
3
Order By: Relevance
“…Its function is not entirely known yet. The results obtained in this work are not consistent with the results of Yano et al (1995) or Kim et al (2008), who detected an increase of NDPK during germination and seedling growth. However, Harris et al (1994) detected the up-regulation of NDPK as a result of stress response, which suggests that the role of NDPK in plants is diversified and needs further investigation.…”
Section: Metabolismcontrasting
confidence: 99%
“…Its function is not entirely known yet. The results obtained in this work are not consistent with the results of Yano et al (1995) or Kim et al (2008), who detected an increase of NDPK during germination and seedling growth. However, Harris et al (1994) detected the up-regulation of NDPK as a result of stress response, which suggests that the role of NDPK in plants is diversified and needs further investigation.…”
Section: Metabolismcontrasting
confidence: 99%
“…However, Kaur et al (1998) found that GA 3 was more effective than CTK in enhancing the reduced germination and seedling growth of chickpea seeds under salt stress. GA synthesis affects not only alterations in protein expression, but also increases in germination rate, promotes root and shoot length during seed germination, and promotes early seedling development (Gallardo et al, 2002;Kim et al, 2008). In the present study, GA content was significantly reduced and seed germination time was delayed by salt.…”
Section: Phytohormonesmentioning
confidence: 48%
“…Recent evidence has suggested a role for the ubiquitin-proteasome pathway in CTK, GA, and ABA signalings (Itoh et al, 2003). 26S ubiquitin-proteasome regulatory subunit 4 homolog levels were increased during rice seed germination by GA and ABA (Kim et al, 2008). Spots 1, 3, 14, and 16 were up-regulated by salt in N2899 and were unaffected in Lee68.…”
Section: Differentially Expressed Proteinsmentioning
confidence: 86%
See 1 more Smart Citation
“…Proteomics have been applied to investigate seed germination in many species, such as Arabidopsis (Arabidopsis thaliana; Gallardo et al, 2001Gallardo et al, , 2002Galland et al, 2014), rice (Oryza sativa; Yang et al, 2007), and pea (Pisum sativum; Wang et al, 2012b). These studies focused on seed germination at the optimal temperature under normal conditions or in response to chemical treatments, such as GA (Gallardo et al, 2002;Kim et al, 2008), ABA (Kim et al, 2008), and salicylic acid (Rajjou et al, 2006), and environmental stress, such as salinity (Yacoubi et al, 2011(Yacoubi et al, , 2013. To the best of our knowledge, no proteomic study has examined the effect of temperature on seed germination.…”
mentioning
confidence: 99%